A comparison of the sense of place between two urban heritage sites (Oudlajan historic neighborhood, Tehran, and Shah Abol-Ghasem, Yazd) - Arash Mohammad-Moradi; Seyed-Abbas Yazdanfar; Mohammad-Ali Khanmohammadi; Saeid Norouzian-Maleki; Paria Shaheen (Frontiers of Architectural Research)
The contemporary era has witnessed damage to the various dimensions of the sense of place in numerous historic and urban heritage sites, which has led to issues such as the disruption of urban life, neglected aspects of the urban poor, and abandonment. This study aims to identify the most important factors contributing to the sense of place in historic fabrics in the present day. A comparative analysis is carried out on the two neighborhoods of Imamzadeh Yahya in Tehran (a progressively dilapidated neighborhood), and Shah Abol-Ghasem in Yazd (with continuity of urban life). The assessment of the residents’ sense of place in the two neighborhoods (n1 = 271) and (n2 = 267) was carried out using the questionnaire tool, and the contributing factors were determined. The results of the two cases were compared using a one-way analysis of variance (ANOVA). The findings showed that the sense of place in Imamzadeh Yahya, with a significant difference (P = 0.00), is at a much lower level than in Shah Abol-Ghasem. Also, most of the factors affecting the sense of place in Imamzadeh Yahya were significantly different (P < 0.05) and at a much lower level compared to Shah Abol-Ghasem, as assessed by the inhabitants.